More than two decades after the introduction of limnoperna fortunei (Dunker 1857) in La Plata Basin - Pessotto, M. A. [UNESP] (2018)
The golden mussel, Limnoperna fortunei, is an Asian freshwater bivalve introduced in South America in the beginning of the 1990’s, probably through ballast water releases in La Plata River estuary. It dispersed north through Paraná, Uruguay and Paraguay Rivers. The study evaluated the macroscale (18° to 34° S; 45° to 60° W) distribution of L. fortunei (larval stages) in the main rivers and reservoirs of La Plata Basin. Samplings were performed through 68 µm vertical plankton net hauls. Limnological variables were simultaneously determined. Larvae abundance correlated significantly with oxygen (positively) in summer, with temperature (positively) in winter and with total phosphorus and total nitrogen (both negatively) in winter. We expected densities to decrease towards north (latitudinal gradient) and increase in lentic conditions (reservoirs). Despite maximum density was found near the introduction point (La Plata River) similar value was also observed 2,000 km north (Paraguay River). The first hypothesis was refuted. The second hypothesis was partially accepted. Abundances were consistently higher in summer. Higher trophic conditions and fast flow seem to inhibit population growth. Food resources (chlorophyll a) locally influenced temporal variation. Limnoperna fortunei is widely distributed in La Plata basin, reaching high larval densities superior to 10,000 ind. m-3, in all major sub-basins. The species exhibits a high intrinsic dispersal ability (free planktonic larvae), wide tolerance to environmental factors and dispersion is potentialized by natural dispersion processes (e.g. fauna displacement) and human facilitation (e.g. commercial navigation).